PENGARUH BUDAYA ORGANISASI DAN KOMUNIKASI ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PERUSAHAAN UMUM DAMRI CABANG LAMPUNG - Hadi Busri; Rini Loliyani (Universitas Mitra Indonesia, 2023)
ABSTRACTThis study aims to determine the correlation between organizational culture and organizational communication to employee job satisfaction in a national company, the Damri Branch Lampung. The population in this study were all employees who worked at the Damri Branch Lampung with a total population was 69 respondents. The technique of selecting a sample with the entire population as the research sample, so that the number of respondents used as a sample of 69 respondents. The data analysis technique used in this research is multiple linear regression analysis with the help of the SPSS program. This study's results indicate that the results of the f-test hypothesis test have a positive and significant effect simultaneously on organizational culture variables and organizational communication on employee job satisfaction at the national company, the Damri Branch Lampung.Keywords: Organizational Culture, Organizational Communication, Employee Job Satisfaction.